Analysis of Internal Factors of Teachers that Impact Performance (Case Study of Teachers at UPTD SMP Negeri 1 Bireuen) - Rizka Utami, Nandar; Iba, Zainuddin; Syahriani, Endang (peusangan, 2025)
Teacher performance is a benchmark for schools to have good quality. This is influenced by external and internal factors in the teacher. Regarding the serious problems with performance, this study aims to analyze internal factors, namely competence, motivation, and work discipline. With associative research with a quantitative approach and applying path analysis, trying to prove the hypothesis. The study was conducted in September 2024 on 72 teachers at UPTD SMP Negeri 1 Bireuen. The results found; (1) there is a causal relationship between the internal factors studied with a moderate category. (2) teacher competence has a significant impact on teacher performance with a contribution of 13.22%. (3) Teacher motivation has a greater influence on teacher performance, which is 20.97%. (4) Discipline has a significant impact on teacher performance with a contribution of 11.04%. (5) Simultaneously, competence, motivation, and discipline have a significant effect on teacher performance with a contribution of 42.5%.